Effect of nozzle angle and air-jet parameters in air-assisted sprayer on biological effect of soybean asian rust chemical protection - De Souza Christovam, Rafael [UNESP]; Raetano, Carlos [UNESP]; De Amaral Dal Pogetto, Mário [UNESP]; Prado, Evandro [UNESP]; Júnior, Hélio [UNESP]; Gimenes, Marcelo [UNESP]; Serra, Marina [UNESP] (Polish Academy of Sciences Chancellery, 2010)
Aiming at improving the efficiency control of Phakopsora pachyrhizi, this research evaluated different application techniques, using spray deposits and yield parameters of soybean crop. Two experiments were carried out in the experimental area of FCA/UNESP - Botucatu, SP, Brazil, in the soybean crop, Conquista variety, in the 2006/2007 season. The first experiment was arranged in random blocks with eight treatments and four replications. The treatments were conducted in factorial arrangement 4×2 (four air levels 0, 9, 11 and 29 km/h combined at two nozzle angles 0 and 30°) using AXI 110015 nozzles. Ten plants on each plot were selected for sampling spray deposits. Artificial targets were fixed on plants, two in the top and another two in the bottom part of plants (abaxial and adaxial leaf surface each one). For deposit evaluations, a cupric tracer was used and the amount of deposits was determined by a spectrophotometer. The second experiment was carried out in the same place and the treatments were of the same arrangement as the previous experiment, including control treatment (untreated plants). The spraying with triazole fungicide was realized in R2 and R5.2 growth stages of soybean with 142 l/ha spray volume. The nozzle angled of 30° combined with maximum air speed promoted the highest spray deposits on the soybean crop and influenced positively the control of the soybean Asian rust as well in the productivity of this crop.
Keywords: application technology; disease; sprayer boom angle; Glycine max; Phakopsora pachyrhizi